Manajemen Pemanenan Kelapa Sawit (Elaeis Guineensis Jacq.) di Divisi II Kebun Seunagan PT. Socfindo - Ogi Prayuda; Muhammad Afrillah; Siti Amina; Amda Resdiar; N.C. Ritonga; Mawaddah Putri Arisma Siregar (Universitas Teuku Umar, 2022)
Palm oil (Elaeis guineensis jacq) is Indonesia's main plantation crop, this plant has greater vegetable oil than other plants, the use of palm oil is in great demand in various industries such as the food industry, the pharmaceutical industry, to the cosmetic industry. The purpose of this study was to determine the management of harvesting carried out in Division II Seunagan Gardens PT. Socfindo. The research was carried out in Division II Seunagan Gardens PT. Socfindo from February to May 2022. Observations made in this harvest management include, Personal protective equipment (PPE) and fresh fruit bunches (FFB) harvesting equipment, calculating harvest density figures (AKP), harvest rotation, estimation of employee usage and daily production estimation, criteria for fruit maturity level, fruit quality observation, random quality observation, determination of premium prices and the number of bases in each block. The results of observations that have been made indicate that the management of oil palm harvesting at PT. Socfindo Seunagan Gardens has been running optimally, this is shown by the very good criteria in several harvesting activities observed, such as harvest rotation, fruit quality criteria, and blok quality